Histological and Immunohistochemical Characterization of Vomeronasal Organ Aging in Mice - Violaine Mechin (Animals, 2021)
The vomeronasal organ (VNO) plays a crucial role in animal behavior since it is responsible for semiochemical detection and, thus, for intra- and interspecific chemical communication, through the vomeronasal sensory epithelium (VNSE), composed of bipolar sensory neurons. This study aimed to explore a well-recognized cause of neuronal degeneration, only rarely explored in this organ: aging. Murine VNOs were evaluated according to 3 age groups (3, 10, and 24 months) by histology to assess VNSE changes such as cellular degeneration or glycogen accumulation and by immunohistochemistry to explore nervous configuration, proliferation capability, and apoptosis with the expression of olfactory marker protein (OMP), Gαi2, Gαo, Ki-67, and cleaved caspase-3 proteins. These markers were quantified as percentages of positive signal in the VNSE and statistical analyses were performed. Cellular degeneration increased with age (p < 0.0001) as well as glycogen accumulation (p < 0.0001), Gαo expression (p < 0.0001), and the number of cleaved-caspase3 positive cells (p = 0.0425), while OMP and Gαi2 expressions decreased with age (p = 0.0436 and p < 0.0001, respectively). Ki67-positive cells were reduced, even if this difference was not statistically significant (p = 0.9105). Due to the crucial role of VNO in animal life, this study opens the door to interesting perspectives about chemical communication efficiency in aging animals.